Isoflavones supplementation of a probiotic soy product: effects on quality characteristics and isoflavones profile - Cavallini, Daniela Cardoso Umbelino [UNESP]; Roselino, Mariana Nougalli [UNESP]; Manzoni, Marla Simone Jovenasso [UNESP]; Pauly-silveira, Nadiége Dourado [UNESP]; Sylos, Célia Maria de [UNESP]; Rossi, Elizeu Antonio [UNESP] (Universidade Estadual Paulista (Unesp), 2010)
The aim of the present study was to investigate the effect of isofl avones supplementation of a fermented soy product on its sensory acceptance, physicochemical properties and probiotic cell viable count. Additionally we also investigated the ability of the mixed starter cultures (Enterococcus faecium CRL 183 and Lactobacillus helveticus 416) to modify the isofl avones profi le of soy product during the fermentation process. Three products were analysed: soy product fermented with E. faecium CRL 183 and L. helveticus 416, isofl avonessupplemented soy product (fermented with E. faecium CRL 183 and L. helveticus 416; 50mg/100g, Isofl avin®, Galena, Brazil) and unfermented soy product. A panel of judges evaluated the acceptability of the samples on a nine point structured hedonic scale. The chemical composition namely fat, protein, ash and total carbohydrate contents, pH, enumeration of viable Lactobacillus spp. and Enterococcus spp. and quantifi cation of isofl avones using HPLC were investigated. All determinations were conducted after 7 days storage at 10°C. The sensorial acceptance was reduced in the isofl avones-supplemented soy product, but this effect was not signifi cant compared to the sample without isofl avones addition. Chemical composition did not differ (p<0.05) among the samples. Cell viable counts were reduced and total fermentation time was longer in the isofl avonessupplemented soy product, suggesting that the isofl avone addition could inhibit the starter cultures. However, all the products may be considered probiotic since they exhibited lactic acid bacterial populations varying from 2.3 x 109 up to 1.22 x 1010 CFU/mL. Fermentation of soymilk did not change the isofl avones profi le. In conclusion, it was possible to obtain a fermented soy product containing a high isofl avones concentration, adequate sensory and chemical characteristics and lactic acid bacterial viability suffi ciently high to characterize the product as a probiotic. The mixed starter culture was not able to convert the glycoside isofl avones into aglycone or produce equol during the fermented soy product processing.

O objetivo desse estudo foi investigar o efeito da suplementação com isofl avonas nas propriedades sensoriais, físico-químicas e microbiológicas de um produto à base de soja fermentado. Em adição, também foi avaliada a habilidade da cultura iniciadora mista (Enterococcus faecium CRL 183 e Lactobacillus helveticus 416) modifi car o perfi l de isofl avonas durante o processo de fermentação. Três produtos foram analisados: produto fermentado (E. faecium CRL 183 e L. helveticus 416), produto fermentado e suplementado com isofl avonas (E. faecium CRL 183 e L. helveticus 416, 50mg/100g de isofl avonas) e produto não fermentado. As amostras foram avaliadas sensorialmente através de um teste de aceitação utilizando escala hedô- nica estruturada de nove pontos. A composição química, (gordura, proteína, cinzas e carboidratos totais), o pH das amostras, a viabilidade dos microrganismos no produto fi - nal e o perfi l de isofl avonas também foram avaliados. Todas as análises foram conduzidas após sete dias de estocagem das amostras a 10°C. A aceitação do produto fermentado suplementado com isofl avonas foi reduzida, porém esse efeito não foi signifi cativo em relação à amostra não suplementada. As amostras apresentaram composição química semelhante. O número de células viáveis foi reduzido e o tempo total de fermentação foi superior para o produto suplementado com isofl avonas, sugerindo que a adição de isofl avonas pode inibir as culturas iniciadoras. Entretanto, todos os produtos fermentados analisados podem ser considerados probióticos, pois apresentaram populações de bactérias láticas variando de 2,3 x 109 a 1,22 x 1010UFC/mL. A fermentação do extrato aquoso de soja não alterou o perfi l de isofl avonas dos produtos. Em conclusão, o presente trabalho possibilitou a obtenção de um produto fermentado de soja contendo concentração elevada de isofl avonas, características sensoriais e químicas adequadas e número de bactérias láticas viáveis sufi ciente para caracterizar o produto como probiótico. A cultura iniciadora mista não foi capaz de converter as isofl avonas glicosídicas em agliconas ou de produzir equol durante o processamento dos produtos.
Suplementação de um produto fermentado de soja probiótico com isofl avonas: efeitos nas características de qualidade e no perfil de isoflavonas
Keywords: Fermented soy product; Isofl avones; Probiotic; Sensorial properties; Produto fermentado de soja; Iso-fl avonas; Probiótico; Ropriedades sensoriais